By counting cause you can find your answer duh
Answer:
(-9, 10)
Step-by-step explanation:
The location of the midpoint of a line with endpoint at (
) and (
) is given as (x, y). The location of x and y are:
![x = \frac{x_1+x_2}{2},y=\frac{y_1+y_2}{2}](https://tex.z-dn.net/?f=x%20%3D%20%5Cfrac%7Bx_1%2Bx_2%7D%7B2%7D%2Cy%3D%5Cfrac%7By_1%2By_2%7D%7B2%7D)
Given the endpoint (9,8) and Midpoint (0,9), the location of the other endpoint can be gotten from:
![0=\frac{9+x_2}{2}\\ \\9+x_2=0\\\\x_2=-9\\\\Also,9=\frac{8+y_2}{2}\\ \\8+y_2=18\\\\y_2=18-8\\\\y_2=10](https://tex.z-dn.net/?f=0%3D%5Cfrac%7B9%2Bx_2%7D%7B2%7D%5C%5C%20%5C%5C9%2Bx_2%3D0%5C%5C%5C%5Cx_2%3D-9%5C%5C%5C%5CAlso%2C9%3D%5Cfrac%7B8%2By_2%7D%7B2%7D%5C%5C%20%5C%5C8%2By_2%3D18%5C%5C%5C%5Cy_2%3D18-8%5C%5C%5C%5Cy_2%3D10)
Hence the endpoint is at (x2, y2) which is at (-9, 10)
The answer is 3n^2+1
9n^2 - 6n^2 = 3n^2
3n-3n=0
4-3=1
Answer:
Step-by-step explanation:
x-y=7
-3x+9y=-39
Divide the second equation by 3
-x +3y = -13
Add this to the first equation
x-y=7
-x +3y = -13
----------------------
0x +2y = -6
Divide by 2
2y/2 = -6/2
y = -3
Now find x
x-y = 7
x -(-3) = 7
x+3 = 7
Subtract 3 from each side
x = 4
(4,-3)
Or by substitution
x-y=7
solve for x
x = 7+y
-3x+9y=-39
Substitute y+7 in for x
-3(7+y) +9y = -39
Distribute
-21 -3y +9y = -39
Combine like terms
-21 +6y = -39
Add 21 to each side
6y = -18